Smokeless Tobacco use among Male and Female in Northeast State, India (Global Journal of Medical Research, 2016)
Smokeless tobacco has been found as harmful as smoke tobacco. Smokeless tobacco associated with the various oral diseases including mouth cancer and adverse reproductive outcome. Objective of this study is to examine the prevalence of smokeless tobacco consumption in Northeast state, India and to study the socioeconomic, demographic correlates of tobacco use in the form of smokeless tobacco only. We used the cross sectional survey DLHS-4 (2012-2013) data of northeast state, India. All men and women living in the study area, aged 15 years and above were included. Information on socio demographic characteristics and smokeless tobacco consumption was administered. Smokeless tobacco consumption was categorized as 'Current consumers' and "non consumers". Associations between smokeless tobacco consumption and the explanatory variables were examine using bivariate and multivariate statistical technique. 67,930 individual men and 75,799 individual women were the unit of analysis in the study. The prevalence of 'Current consumption' among men 65% and women 51% respectively. Current consumption was associated with level of education, religion, caste, occupation, residence, marital status, and age.
Keywords: cross sectional study; men; women; smokeless tobacco and Northeast state